HEAT EXCHANGER NETWORK ANALYSIS AT CRUDE DISTILLATION UNIT - Ramdhani, Dendi
To heat the feed stream into the fractionation column in the CDU, furnace uses fuel, which is the major cost of operating the CDU preheat. CDU (Crude Distillation Unit) has 11 heat exchanger in the pre-heat crude process before crude enter the field to reduce the furnace burden. In order to save operating costs, particularly in the use of fuel for the furnace, it is required an optimization of heat exchanger network (HEN) that lightering the furnace burden. The possibilities of optimizing to increase the furnace inlet temperature are necessary for the investigation. Therefore, an analysis of the current state and possibility to do the optimization of heat exchanger network configurations (HEN) becomes important. The approach that is applied in this thesis includes the thermodynamic analysis, the input and output of components exist in the system that are analyzed, the heat exchanger network in the system and then optimized by using the method of "Pinch Technology". The results of calculations based on data taken on Desember 19, 2012 are presented in the form of "Grid Heat Exchanger Network", efficiency and lost exergy value. Test results of research show the optimum design is obtained using a software Aspen Energy Analyzer V.7.3 with heating energy saving and cooling energy saving at 27,31% and 47,88%. While from exergy analysis, lost exergy resulting reduction at 62,45%